THE ROLE OF HUMAN RESOURCE MANAGEMENT IN ORGANIZATIONS - JFX Susanto Soekiman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Human Resource Management (HRM) plays a pivotal role in the success and sustainability of modern organizations. This abstract provides an overview of the key aspects of HRM and its significance within organizational contexts. HRM encompasses a wide range of functions, including recruitment and selection, training and development, performance appraisal, compensation and benefits, and employee relations. Effective HRM practices contribute to improved employee morale, enhanced productivity, and ultimately, the attainment of organizational goals. Furthermore, HRM is instrumental in fostering a positive workplace culture, promoting diversity and inclusion, and aligning the workforce with the strategic objectives of the organization. This abstract explores the multifaceted nature of HRM, its evolving role in a dynamic business environment, and the challenges and opportunities it presents for organizations seeking to thrive in the 21st century. Understanding the strategic significance of HRM is essential for organizations looking to navigate the complexities of today's competitive landscape and achieve long-term success. Keywords: Human Resource Management (HRM), organizational success, training and Development